If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -1(-15) = 21 Multiply -1 * -15 m + 15 = 21 Reorder the terms: 15 + m = 21 Solving 15 + m = 21 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + m = 21 + -15 Combine like terms: 15 + -15 = 0 0 + m = 21 + -15 m = 21 + -15 Combine like terms: 21 + -15 = 6 m = 6 Simplifying m = 6
| 1/3(a+1)=1/6(3a-5) | | 14m+26=28m+19 | | 2x^2-17+30=0 | | 14f+26=28f+19 | | 15x^2+14x-8= | | 3a+2-5a=-24 | | 7m+3[m+2]=-24 | | 9x^2+24x+144=20 | | 15x=100+10x | | 2m=sm+5 | | -7b+6(7-b)=-6b+4(b-6) | | 15x^2+x-6= | | y=3.5x-2.7 | | x^3+2x^2-33x-34=0 | | 6a+12=6a-8 | | 14+26=28+19 | | x^4-16x^2+75=2X^2-6 | | 23=-5m+2 | | b=2x+y | | 4+p=2 | | 1x=x+1 | | 6-5n=24 | | 0.25((28)-12)=4 | | (3x^2)-2x-1= | | 6+3v=5v+16 | | 0=x^2+2x-99 | | (3x^2)+4x+1= | | 6y+16=2(4y+3) | | x+1=9x^3+9x | | x+3y=120 | | 10s=5s+60 | | 17x-16=10x-63 |